Analisis Kandungan Vitamin C Dan Kalium Dalam Labu Kuning (Cucurbita Moschata) - Setiawan, Heri; Sabang, Sri Mulyani; Tangkas, I Made (Universitas Tadulako, 2014)
Research has been conducted to determine the level of vitamin C by a visible spectrophotometer, and a metal content of potassium (K) from pumkin sample (Cucurbita Moschata) by Atomic Absorption Spectrophotometer (AAS). Measuring the levels of vitamin C in the sample performed at a wavelength (Î») = 510 nm and measuring the levels of potassium in the sample performed at a wavelength (Î») = 766,5 nm. The results obtained by the levels of vitamin C is sample A (pumpkin from Jono oge village) obtained at 6 mg/L, sample B (pumpkin from Sidera village) obtained at 4,5 mg/L, and sample C (pumpkin from Toro village) obtained at 0,97 mg/L. While the metal content of potassium is sample A (pumpkin from Jono oge village) obtained at 23,22 mg/L, sample B (pumpkin from Sidera village) obtained at 22,22 mg/L, and sample C (pumpkin from Toro village) obtained at 20,22 mg/L. These data indicate that the levels of vitamin C and potassium sample A higher than sample B and C.